Neuroglobin in Retinal Neurodegeneration: A Potential Target in Therapeutic Approaches - Virginia Solar Fernandez (MDPI AG, 2021)
Retinal neurodegeneration affects an increasing number of people worldwide causing vision impairments and blindness, reducing quality of life, and generating a great economic challenge. Due to the complexity of the tissue, and the diversity of retinal neurodegenerative diseases in terms of etiology and clinical presentation, so far, there are no cures and only a few early pathological markers have been identified. Increasing efforts have been made to identify and potentiate endogenous protective mechanisms or to abolish detrimental stress responses to preserve retinal structure and function. The discovering of the intracellular monomeric globin neuroglobin (NGB), found at high concentration in the retina, has opened new possibilities for the treatment of retinal disease. Indeed, the NGB capability to reversibly bind oxygen and its neuroprotective function against several types of insults including oxidative stress, ischemia, and neurodegenerative conditions have raised the interest in the possible role of the globin as oxygen supplier in the retina and as a target for retinal neurodegeneration. Here, we provide the undercurrent knowledge on NGB distribution in retinal layers and the evidence about the connection between NGB level modulation and the functional outcome in terms of retinal neuroprotection to provide a novel therapeutic/preventive target for visual pathway degenerative disease.